CRISPR/Cas9 Genome Editing to Disable the Latent HIV-1 Provirus - Panfil, Amanda R.; London, James A.; Green, Patrick L.; Yoder, Kristine E. (Frontiers in Microbiology, 2018)
HIV-1 infection can be successfully controlled with anti-retroviral therapy (ART), but is not cured. A reservoir of cells harboring transcriptionally silent integrated provirus is able to reestablish replicating infection if ART is stopped. Latently HIV-1 infected cells are rare, but may persist for decades. Several novel strategies have been proposed to reduce the latent reservoir, including DNA sequence targeted CRISPR/Cas9 genome editing of the HIV-1 provirus. A significant challenge to genome editing is the sequence diversity of HIV-1 quasispecies present in patients. The high level of quasispecies diversity will require targeting of multiple sites in the viral genome and personalized engineering of a CRISPR/Cas9 regimen. The challenges of CRISPR/Cas9 delivery to the rare latently infected cells and quasispecies sequence diversity suggest that effective genome editing of every provirus is unlikely. However, recent evidence from post-treatment controllers, patients with controlled HIV-1 viral burden following interruption of ART, suggests a correlation between a reduced number of intact proviral sequences and control of the virus. The possibility of reducing the intact proviral sequences in patients by a genome editing technology remains intriguing, but requires significant advances in delivery to infected cells and identification of effective target sites.